Group Counseling With Stress Inoculation Training To Improve Students’ Coping Stress - Nimas Ayu Salsabilla; Ulvina Rachmawati; Iqbal Tawakkal; Zeti Novitasari (Universitas Negeri Semarang, 2024)
Covid 19 has transformed the lecture system from offline to online and now to blended. While there are changes in the lecture system, students are still required to get a high GPA and the timeliness of graduation encourages students to experience stress. Stress can be overcome immediately if students have high coping stress, otherwise students can get depressed and even commit suicide. This research aims to improve student coping stress by using group counseling stress inoculation coping (SIT). This study involved 8 students from Nahdlatul Ulama Sunan Giri University as the subjects and the data collection used coping stress scale while data analysis used non-parametric statistic, Wilcoxon test. The result shows 61% of students have moderate stress coping, 16% high, and 23% low. Wilcoxon test shows Asymp. Sig 0.012 on coping stress, problem focused coping, and emotional focused coping. More specifically, Wilcoxon test shows 1) Asymp. Sig 0.011 on seeking information support, planful problem solving; distancing, self-control, and accepting responsibility; 2) Asymp. Sig value 0.012 on confrontative coping; 3) Asymp. Sig value 0.017 on positive reappraisal; 4) Asymp. Sig 0.093 on ascape; and 5) Asymp. Sig value 0.518 on seeking social emotional. It can be concluded that group counseling stress inoculation training technique is effective to improve stress coping including improving problem focused coping and emotional focused coping. In addition, group counseling is effective for increasing coping stress behaviors such as seeking information support, confrontative coping, planful problem solving, distancing, self-control, accepting responsibility, and positive reappraisal. As well as effective for reducing ascape and seeking social emotional. Covid 19 telah mengubah sistem perkuliahan dari offline menjadi online dan kini menjadi blended. Meski terjadi perubahan sistem perkuliahan, mahasiswa tetap dituntut untuk mendapatkan IPK yang tinggi dan ketepatan waktu kelulusan mendorong mahasiswa mengalami stres. Stres dapat segera diatasi apabila siswa mempunyai coping stress yang tinggi, sebaliknya siswa dapat mengalami depresi bahkan bunuh diri. Penelitian ini bertujuan untuk meningkatkan coping siswa terhadap stres dengan menggunakan konseling kelompok stress inoculation coping (SIT). Penelitian ini melibatkan 8 orang mahasiswa Universitas Nahdlatul Ulama Sunan Giri sebagai subjek dan pengumpulan data menggunakan coping stress scale sedangkan analisis data menggunakan statistik non parametrik, uji Wilcoxon. Hasil penelitian menunjukkan 61% siswa mempunyai coping stres sedang, 16% tinggi, dan 23% rendah. Tes Wilcoxon menunjukkan Asymp. Sig 0,012 pada coping stres, coping fokus masalah, dan coping fokus emosional. Lebih spesifiknya uji Wilcoxon menunjukkan 1) Asymp. Sig 0,011 pada pencarian dukungan informasi, pemecahan masalah secara terencana; menjaga jarak, pengendalian diri, dan menerima tanggung jawab; 2) Asimp. Nilai sig 0,012 pada coping konfrontatif; 3) Asimp. Nilai sig 0,017 pada penilaian kembali positif; 4) Asimp. Sig 0,093 pada ascape; dan 5) Asimp. Nilai sig 0,518 pada pencarian sosial emosional. Dapat disimpulkan bahwa teknik pelatihan inokulasi stres konseling kelompok efektif untuk meningkatkan koping stres termasuk meningkatkan koping yang berfokus pada masalah dan koping yang berfokus pada emosional. Selain itu, konseling kelompok efektif untuk meningkatkan perilaku coping stres seperti mencari dukungan informasi, coping konfrontatif, pemecahan masalah secara terencana, menjaga jarak, pengendalian diri, menerima tanggung jawab, dan penilaian ulang yang positif. Serta efektif untuk mengurangi pelarian dan pencarian emosi sosial.